Strong Convergence of a Projected Gradient Method - Shunhou Fan; Yonghong Yao (Journal of Applied Mathematics)
The projected-gradient method is a powerful tool for solving constrained convex optimization problems and has extensively been studied. In the present paper, a projected-gradient method is presented for solving the minimization problem, and the strong convergence analysis of the suggested gradient projection method is given.